'Distorted gravity: The intensive and extensive margins of international trade' revisited ; an application to an intermediate Melitz model - Sören Prehn; Bernhard Brümmer (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2011)
With the extension of the standard Melitz Model from Ahn et al. [2011], the important role of intermediaries in facilitating trade is now recognized. In this paper, we are going to expand Chaney's [2008] approach to an Intermediate Melitz Model. By researching if Chaney's results still apply for an Intermediate Melitz Model, main results of Chaney are confirmed for the direct export model, but this is not so for the indirect export mode. Here, the elasticity of substitution still dampens the extensive margins; however, whether the dampening effect on the extensive margin still dominates the magnifying effect on the intensive margin is ambiguous. Also, the elasticities of trade ows are no longer larger, but rather smaller than in the Krugman Model. All results are economically meaningful.
Keywords: 330; international trade; Intermediate Melitz Model; firm heterogeneity; elasticities of trade flows; extensive and intensive margins; Außenwirtschaft; Gravitationsmodell